Complement activation by cellulosic dialysis membranes. Issue 2 (February 1994) - Innes, A; Farrell, A M; Burden, R P; Morgan, A G; Powell, R J
Abstract : AIMS--To assess the effect of cellulosic dialysis membranes on the production of complement degradation products to determine to the role of the classical pathway. METHOD--Complement activation was studied in 33 patients during a single haemodialysis session using cellulosic membranes. Pre- and post-dialysis plasma EDTA valves of C3, C4, C3dg, C4d and C reactive protein (CRP) were measured. Statistical analysis was done using the Wilcoxon signed rank test. RESULTS--Post-dialysis C4 (p = 0.0003), C3dg (p < 0.0001), and C4d (p = 0.003) concentrations were increased compared with pre-dialysis values. There was no significant change in C3 (p = 0.095) and CRP (p = 0.13) values. Post-dialysis C3dg and C4d concentrations correlated significantly (p = 0.007). IgG, an undialysed molecule, was quantified and post-dialysis valves were significantly higher than those before dialysis (p = 0.0002), indicating a degree of haemoconcentration. To remove this effect, the C3:IgG, C4:IgG, C3dg:IgG, C4d:IgG and CRP:IgG ratios were calculated. Compared with pre-dialysis values, post-dialysis C3dg:IgG and C4d:IgG ratios were increased and C3:IgG decreased significantly. No change was observed in C4:IgG and CRP:IgG ratios. CONCLUSION--This study confirms that significant complement activation takes place following dialysis with cellulosic membranes. This is denoted by an increase in C3dg. This was paralleled by a rise in C4d, implying a contributory role for the classical pathway. Concomitant post-dialysis increases in IgG and C4 indicate a degree of haemoconcentration; but removal of this effect shows that C3dg and C4d are increased following dialysis--suggesting classical, in addition to alternative, pathway activation.